Blood Bank Service: An Experience at Karnali Academy of Health Sciences, Jumla, Nepal (MedS Alliance Journal of Medicine and Medical Sciences, 2021)
INTRODUCTION: In January 2016, Karnali Academy of Health Sciences (KAHS) began providing blood bank services to the Red Cross Society of Jumla. The purpose of this study was to investigate the most prevalent blood group in the study area. We must know the blood group based on the demand for blood in order to store the most common blood group and compile a donor list.MATERIALS AND METHODS: The retrospective study was done between 1 June 2021 and 30 November 2021 at KAHS JUMLA. We are required to donate whole blood to various departments at Karnali Academy of Health Science (KAHS), Jumla. Blood group and socio-demographic profile was collected. Descriptive analysis performed using Excel software.RESULTS: Out of 500 transfusion units dispatched, 416 (83.2%) were male and 84(16.8%) were female. Out of 500 units of blood, most common blood group is A +ve which was 175 and 2nd most common blood group was O+ve which was 115 (23.0%) followed by B+ve which was 111 (22.2%).The rarest blood group was B-ve which is 5 (1.0%).CONCLUSIONS: The most common blood group demand by patient was B +ve. The most frequent demand came from gynecological department followed by surgery and orthopaedics department. Hence, the findings may help for the planning and storing the required amount of blood by blood group for KASH to meet the future demand.